Retrospective study of characteristics and management of pyogenic liver abscess during 5 years’ experience - Zhou, Yuanyuan (Int J Clin Exp Pathol, 2021)
Pyogenic liver abscess is a life-threatening disease. It is urgent to review the clinical patterns, risk factors, and management of the disease in order to improve the outcome. We retrospectively analyzed 70 cases of pyogenic liver abscess diagnosed and treated at Shanghai Ninth People’s Hospital over five years, including the clinical features, management, and outcome. The average age was 63.06 ± 12.33 y. 71.4% (50/70) were males. 85.7% (60/70) patients presented with fever. The major abnormalities in laboratory were increased CRP and liver dysfunction. 77.8% (14/18) pus cultures came with positive reports, while 26.5% (9/34) blood cultures were positive. K. pneumoniae was the predominant pathogen both in blood (66.7%, 6/9) and pus (64.3%, 9/14) cultures. 42.9% (30/70) patients also had diabetes. Patients with diabetes presented with significantly larger size of abscess (P = 0.014) and were more susceptible to K. pneumoniae infection (P = 0.002). We revealed HbA1c (P = 0.047), accompanying malignancy (P = 0.030), and septic shock (P = 0.045) were three independent risk factors for PLA. In conclusion: pyrogenic liver abscess was atypical; microbiologic positivity of pus culture was higher than that of blood culture; K. pneumoniae was the predominant pathogen in pyrogenic liver abscesses, especially in patients with diabetes; and patients with hyperglycemia had poor outcome.